Glacial landforms around the boundary between the central and northern Black Forest, south-western Germany - Felix Martin Hofmann; Leo Vorwerg; Robert Witschel (PANGAEA, 2025)
The aim of data collection was the reconstruction of the chronology and extent of the Late Pleistocene glaciation around the boundary between the central and northern Black Forest. This research has been undertaken as part of the extquotesingleChronology of the last glaciation of low mountainous areas in Central Europe extquotesingle project (funded by the German Research Foundation (DFG)). This project is granted to Felix Martin Hofmann (see https://gepris.dfg.de/gepris/projekt/534739108?language=en, last access: 13 June 2025). As a first step towards comprehensive glacier reconstruction, glacial geomorphological mapping according to present-day standard in the field of glacial geomorphology must be undertaken, allowing for the selection of suitable targets for dating campaigns. Previous cirque and moraine mapping led to valuable datasets but the adopted approach for the acquisition of data does not comply with up-to-date approaches in geomorphological mapping. Hence, a mapping campaign was undertaken to critically evaluate previous work on the region of interest to achieve the greatest possible accuracy during mapping. The acquired data represent the base of a manuscript which has been submitted to the Journal of Geomorphology for consideration for publication.